Analysis of the Implementation of Private Entity Financial Accounting Standards (SAK EP) in Financial Reports at BMT Assafi'iyah Berkah Nasional Tanjung Jaya Branch Office - Adam Charisna Putra; Ika Trisnawati Alawiyah; Haris Santoso (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The development of accounting practices in the microfinance sector requires every entity to prepare financial statements that are accurate, transparent, and reliable. The quality of accounting information plays an essential role in evaluating institutional performance, managing assets, and supporting decision-making by stakeholders. To improve the transparency and accountability of financial reporting for entities without significant public accountability, the Indonesian Institute of Accountants (IAI) introduced the Financial Accounting Standards for Private Entities (SAK EP) as a refinement of SAK ETAP. This standard is designed to be simpler and more applicable to private entities, including Baitul Maal wat Tamwil (BMT). This study aims to analyze the implementation of SAK EP in the financial statements of BMT Assyafi'iyah Berkah Nasional, Tanjung Jaya Branch Office, and to identify its compliance with the applicable accounting standards. This study employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation. The results indicate that BMT has implemented SAK EP in the recognition, recording, measurement, presentation, and disclosure of financial statements in accordance with the applicable guidelines. The financial statements prepared have included the main components required under SAK EP. However, the implementation has not yet been fully optimized due to several challenges, including adjustments to the chart of accounts, limited human resource competencies in understanding the new standard, and the need to adjust accounting treatments for transactions based on Sharia contracts. Overall, the implementation of SAK EP has improved the quality of financial statements by making them more relevant, reliable, transparent, and accountable, thereby strengthening institutional governance and enhancing the confidence of members and stakeholders in the performance of BMT.